Preferensi Peserta Didik terhadap Umpan Balik Guru pada Kemampuan Menulis Bahasa Inggris di Sekolah Menengah Kawasan Teluk Tomini - Haris Danial; Rahmatan Idul (Jurnal Kajian Bahasa, Sastra dan Pengajaran (KIBASP), 2020)
This study aims to 1) Identify the problems and needs of students towards teacher feedback on English Writing Skills at Tomini Bay Middle Schools; 2) Analyze what kind of teacher feedback preferences students want on English Writing Ability at Tomini Bay Area Secondary Schools; 3) Develop students' preferences for teacher feedback on English Writing Ability at Tomini Bay Area Middle School. This study describes the results of student preferences for teacher feedback on the results of English writing in the Tomini Bay area secondary schools based on the results of data in the form of numbers that show the most dominant priority and become the choice of students towards the aspects that are in the feedback of teacher to the students' writing. The results of this study indicate that the results of the analysis of the recapitulation of the dominance of the teacher's feedback category on students 'written English, the students' preferences for teacher feedback emphasize more direct feedback, namely the teacher writes the correct or approaching error correction form and provides a brief explanation of the answer is wrong. This analysis shows that students prefer to have direct feedback because from the score obtained the highest average score is in the type of direct feedback. Keywords: Student Preferences, Teacher Feedback, English Writing Ability